Magnetic and electric properties of wrinkled manganite films derived by sol‐gel method. Issue 6 (2nd May 2017) - Zhao, Bo; Chen, Ying; Xue, Fen; Guo, Xin; Wang, Genshui; Yang, Lihui; Wang, Wensheng; Dong, Xianlin
Abstract: Flat and wrinkled La0.7 Sr0.3 MnO3 (LSMO) thin films were prepared by sol‐gel method, respectively, on Si (001) substrates by adjusting heating rate at drying stage. Wrinkled film has larger grains than flat film. Coercive field (about 27 Oe) of wrinkled film is higher than that of flat film, which is much low as around 5 Oe. Compared with flat films, wrinkled films have larger magnetization, higher Curie temperature (334 K) and peak resistivity temperature (243 K), and lower resistivity (0.18 Ohm·cm at 300 K). The introducing of wrinkles is an efficient way to induce compressive stress in sol‐gel derived polycrystalline LSMO films and enhance the magnetic and electric properties.